2022
DOI: 10.1093/nar/gkac458
|View full text |Cite
|
Sign up to set email alerts
|

An in-library ligation strategy and its application in CRISPR/Cas9 screening of high-order gRNA combinations

Abstract: Simultaneous targeting multiple genes is a big advantage of CRISPR (clustered regularly interspaced short palindromic repeats) genome editing but challenging to achieve in CRISPR screening. The crosstalk among genes or gene products is a common and fundamental mechanism to ensure cellular stability and functional diversity. However, the screening approach to map high-order gene combinations to the interesting phenotype is still lacking. Here, we developed a universal in-library ligation strategy and applied it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…CRISPR-Cas9 K562/Jurkat screens. K562 and Jurkat cell lines expressing Cas9 stably and lentivirus pools carrying sgRNA libraries were produced as previously described 14 . K562-Cas9 cells were cultured in 1640 medium with 10% FBS and 1 μg/ml blasticidin on confluency of 0.5 million/ml in shaking incubators at 120 rpm, 37 °C, and with 5% CO2.…”
Section: Lentiviral Vectors Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR-Cas9 K562/Jurkat screens. K562 and Jurkat cell lines expressing Cas9 stably and lentivirus pools carrying sgRNA libraries were produced as previously described 14 . K562-Cas9 cells were cultured in 1640 medium with 10% FBS and 1 μg/ml blasticidin on confluency of 0.5 million/ml in shaking incubators at 120 rpm, 37 °C, and with 5% CO2.…”
Section: Lentiviral Vectors Constructionmentioning
confidence: 99%
“…These CRISPR-based knockout screening systems have been applied to hundreds of cell types in different organisms 3 , 4 and made significant advancements in unraveling biological processes in many aspects, for example, functional genomics 5 , cancer, and immunotherapy 6 – 9 . Accordingly, many studies have been performed to improve the performance of CRISPR-based knockout screening systems, including CRISPR/Cas enzyme optimization 10 sgRNA library design 11 13 , and sgRNA delivery 14 . However, the sgRNA library size remains a stringent barrier to the application of CRISPR-based knockout screening systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TCR-driven kinases, critical for evaluating T cell responses, can be pinpointed through these screens. In a study targeting 25 TCR-driven kinases within primary T cells, perturbing these kinases revealed that only p38 kinase functioned as a central regulator, influencing T cell phenotypic attributes such as cell expansion, differentiation, response to oxidative stress, and genomic stability [135,136]. In engineered human T cells, the application of CRISPR-Cas9 library screening serves a pivotal role in the identification of primary regulators governing cell fate.…”
Section: Crispr Screen For T Cellsmentioning
confidence: 99%